Corporate financing under moral hazard and the default risk of buyers - Péter Csóka; Dániel Havran; Nóra Szűcs (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
We extend the theoretical model of external corporate financing to the case when the buyers of the borrowing firm may default during the financing period. In our setup there is an asymmetric information and hence moral hazard between the lender and the borrower concerning the effrts of the borrower. We define the optimal debt contract in two cases. In the symmetric case the lender and the borrower has the same information about the buyer, its probability of default. In the asymmetric case the borrower learns whether the buyer will pay or not before choosing her level of efforts. We prove that in the asymmetric case the borrowing capacity and the welfare of the society is weakly smaller than in the symmetric case. We also show that the nonnegative default risk of a buyer weakly decreases borrowing capacity compared to the case when the buyer pays for sure. However, it turns out that having a risky buyer might increase borrowing capacity and welfare.
Keywords: G32; C72; 330; game theory; moral hazard; corporate financing; trade credit